Potential of nanostructured alumina for leaf-cutting ants Acromyrmex lobicornis (Hymenoptera: Formicidae) management - Buteler, Micaela (2018)
The present study assessed the contact toxicity of nanostructured alumina (NSA) and compared it to that of diatomaceous earth (DE) on workers of Acromyrmex lobicornis. Laboratory and field bioassays were also conducted to assess whether ants avoid NSA particles. Nanostructured alumina was more toxic to ants than DE (LC50 for NSA = 0.14 mg/g; CI 0.12–0.17; LC50 for DE = 0.36 mg/g; CI 0.25–0.77). The laboratory bioassays results showed that ants were not repelled by NSA. The average repellence percentage observed in the Petri dish bioassay was 0.66 ± 3.1. No repellence was observed in field tests either, given that ants collected oat flakes treated with NSA (12.7 ± 1.2 oat flakes) in similar amounts to control oats (13.9 ± 1.6 oat flakes) after 2 h. Scanning electron microscope pictures showed that NSA was more effective than DE in attaching to the cuticle of exposed insects. This study reports for the first time the toxicity of NSA on leaf-cutting ants and shows that it has greater efficacy than DE in killing A. lobicornis at all the concentrations tested. Thus, NSA shows potential to be used as a dust insecticide that could be applied directly at the nest to induce mortality of worker ants. Further studies should address the effect of NSA on the symbiotic fungus, as well as its potential as carrier for other insecticides or fungicides.